Nitric Oxide in the Control of the in vitro Proliferation and Differentiation of Human Hematopoietic Stem and Progenitor Cells - Hümmer, Julia; Kraus, Saskia; Brändle, Katharina; Lee-Thedieck, Cornelia (Frontiers in Cell and Developmental Biology, 2021)
Hematopoietic stem and progenitor cell (HSPC) transplantation is the best-studied cellular therapy and successful in vitro control of HSPCs has wide clinical implications. Nitric oxide (NO) is a central signaling molecule in vivo and has been implicated in HSPC mobilization to the blood stream in mice. The influence of NO on HSPC behavior in vitro is however largely obscure due to the variety of employed cell types, NO administration systems and used concentration ranges in literature. Additionally, most studies are based on murine cells which do not necessarily mimic human HSPC behavior. Thus, the aim of the present study was the systematic, concentration-dependent evaluation of NO-mediated effects on human HSPC behavior in vitro. By culture in presence of the long-term NO donor Diethylenetriamine/nitric oxide adduct (DETA/NO) in a non-toxic concentration window, a biphasic role of NO in the regulation of HSPC behavior was identified: Low DETA/NO concentrations activated classical NO signaling, identified via increased intracellular cGMP levels and PKG-dependent VASP phosphorylation, and mediated a pro-proliferative response of HSPCs. In contrast, elevated NO concentrations slowed cell proliferation and induced HSPC differentiation. At high concentrations, s-nitrosylation levels were elevated and myeloid differentiation was increased at the expense of lymphoid progenitors. Together these findings hint at a central role of NO in regulating human HSPC behavior and stress the importance and the potential of the use of adequate NO concentrations for in vitro cultures of HSPCs, with possible implications for clinical application of in vitro expanded or differentiated HSPCs for cellular therapies.